Pengaruh Keterbatasan Sumber Daya Pada Efektivitas Penegakan Hukum Pidana Dalam Menghadapi Tindak Pidana Korupsi - Widianto, Dhanar Panji (Jurnal JURISTIC, 2024)
Resource constraints are one of the challenges in criminal law enforcement related to corruption crimes in Indonesia. This article aims to examine the influence of resource constraints on the effectiveness of criminal law enforcement in dealing with corruption crimes in Indonesia through a literature review method. The results of the study show that resource constraints, whether in the form of budget, expert personnel, or technology, significantly impact the effectiveness of criminal law enforcement against corruption. Budget constraints lead to a lack of operational support, limited facilities and infrastructure, and low incentives for law enforcement officers, which can trigger corrupt practices. Meanwhile, constraints in expert personnel and technology result in slow case handling, lack of strong evidence, and weak monitoring and prevention of corruption crimes. These resource constraints hinder the processes of investigation, inquiry, and prosecution of corruption cases, leading to low case resolution rates and reduced deterrent effects for perpetrators. Therefore, comprehensive efforts are needed to overcome resource constraints, including adequate budget allocation, capacity building of human resources through training and recruitment of experts, and the utilization of modern technology in criminal law enforcement against corruption in Indonesia. These measures are expected to enhance the effectiveness of law enforcement and more optimally eradicate corruption crimes.